2022
DOI: 10.3389/fpsyg.2021.746897
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Accuracy Did Not Affect Moral Decision-Making, but Affect Regret Rating for One’s Moral Choices

Abstract: Previous studies have revealed the effect of interoceptive accuracy (IAcc), a behavioral measure of the ability to feel physiological states and regulation for that, which origin emotion on decision-making such as gambling. Given that decision-making in moral dilemma situations is affected by emotion, it seems that IAcc also affects moral decision-making. The present study preliminarily investigates whether IAcc affects decision-making and emotional ratings such as regret for one’s own choices in moral dilemma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…It is important to note that interoceptive sensitivity does not correlate with the consistency of an individual's utilitarian or deontological decision-making, consistent with recent research (Tamura et al, 2022). Previous studies have reported associations between certain neural structures, particularly the vmPFC, a critical component of the interoceptive neural circuitry, and the ratio of utilitarian or deontological decision choices.…”
Section: Discussionsupporting
confidence: 69%
“…It is important to note that interoceptive sensitivity does not correlate with the consistency of an individual's utilitarian or deontological decision-making, consistent with recent research (Tamura et al, 2022). Previous studies have reported associations between certain neural structures, particularly the vmPFC, a critical component of the interoceptive neural circuitry, and the ratio of utilitarian or deontological decision choices.…”
Section: Discussionsupporting
confidence: 69%